Representasi Maskulinitas Perempuan dalam Serial Televisi The Killing Season 1 - Kristianto, Nugroho; Suharijadi, Didik; Murti, Ghanesya Hari (Universitas Brawijaya, 2024)
This research discusses the representation of female masculinity in the television series The Killing Season 1. The main character, Sarah Linden, is a woman who does not exhibit traditional femininity but rather embodies masculine traits. This study aims to understand how masculinity is represented in Sarah Linden's character in The Killing Season 1. Utilizing John Fiske's semiotic theory, this research reveals the meanings embedded within the semiotic codes. A qualitative approach is employed, with descriptive analysis to interpret the findings. The analysis reveals the presence of masculine characteristics in Sarah Linden, such as no sissy stuff, be a big wheel, be sturdy as an oak, and give 'em hell. These masculine traits reflect ideologies including liberal feminism, anti-patriarchy, masculinism, and feminism, which assert that men and women possess equal capabilities. The study emphasizes gender equality and recognizes the positive contributions of all individuals, regardless of gender.